Brown bast disease of rubber trees - Pushpadas M V (Rubber Board Bulletin, 1995)
The symptoms, causes, mechanism and prevention/cure of brown bast [a disorder of rubber trees now known as tapping panel dryness] are discussed.
Source Year: 1996
Keywords: Brown bast; Hevea brasiliensis; Tapping panel dryness